Diametrically Opposed Carbenes on an α‐Cyclodextrin: Synthesis, Characterization of Organometallic Complexes and Suzuki–Miyaura Coupling in Ethanol and in Water. Issue 18 (18th April 2013) - Guitet, Maxime; Marcelo, Filipa; de Beaumais, Ségolène Adam; Zhang, Yongmin; Jiménez‐Barbero, Jesús; Tilloy, Sébastien; Monflier, Eric; Ménand, Mickaël; Sollogoub, Matthieu
Abstract: Two carbene‐based ligands have been attached to perbenzylated and permethylated cyclodextrins. Their palladium complexes were synthesized, characterized and used as catalysts in Suzuki–Miyaura coupling reactions both in ethanol and water. Abstract : Two carbene‐based ligands have been attached to perbenzylated and permethylated cyclodextrins. Their palladium complexes were synthesized, characterized and used as catalysts in Suzuki–Miyaura coupling reactions both in ethanol and water.